Regional and socio-economic disparity in use of insecticide-treated nets to prevent malaria among pregnant women in Kenya. Issue 3 (29th April 2022) - Haileselassie, Werissaw; Habtemichael, Mizan; Adam, Ruth; Haidar, Jemal; David, Randy E; Belachew, Ayele; Mengesha, Abenet Tafesse; Koepfli, Cristian; Deressa, Wakgari; Parker, Daniel M; Kassaw, Nigussie Assefa
Abstract: Background: Insecticide-treated net (ITN) use is among the most recommended strategies to prevent malaria in pregnancy. We analysed the regional and socio-economic patterns of ITN use among pregnant women in Kenya using data from the 2003, 2008 and 2014 Kenyan Demographic and Health Surveys (KDHSs). Methods: Inequality was assessed using four dimensions: economic status, education, place of residence and region. Both relative and absolute summary measures were applied. In addition, simple and complex summary measures, i.e. difference, population attributable fraction, population attributable risk and ratio were considered based on the number of subgroups in each variable. Results: There was overt inequality in the use of ITNs among pregnant women, with greater use among the better-off group in 2003 and 2014. Greater ITN use was also observed among pregnant women with a higher level of education. Pregnant women from urban settings tended to use ITNs (slept under a net the night before the survey) more than their rural counterparts in the 2003 KDHS. There were significant regional variations across the three surveys in all inequality summary measures, except ratio in the 2014 survey. Conclusions: Significant inequality in ITN use among pregnant women was observed at a macro scale.